EFFECT OF JUMPS IN PROFOUNDNESS ON THE FOOTBALLER REFLECTION - Nebojša Đošić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
The treatment endured one month. For this time 8 trainings and totally 322 jums in profoundness were done with differant altitudes from 42 cm to 105 cm. The complete time of work with time-out between sequences was about 120 minutes. The time-out between the sequences was from 2 ' til 6'. The pause between the training was from 2 to 5 days. The puls after 30 '' from the finishing of the jums in th sequence was from 100 to 140 pulsation in the minute measured by palpation. On the finaly measurement is constated that the two leg jump from place in height was better for 7 cm , and the one leg jump with three footsteps spring was better for 2 cm. This such result indicate on the assumption that the progress must bi greater if the program would be longer , for example two, three months and if this program should be done by footbalers which are active and in the best player years i.e. between 18 -30 year. The author was by this time 40 years old.